(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The research aimed to evalauate the effectiveness of aquatic extract and Alcoholic extracts of seed and roots mustard under laboratory conditions at concentrations of) 0.5, 1, 1.5( %to inhibiting the eggs’ hatching and viability of second-stage juveniles (J2). The results indicated that the Alcoholic extract of mustard seeds at a concentration of 1.5% showed effectiveness in reducing egg hatching after (24 ,48, 72) (h) with percentages of (32, 67.67, 88) compared to the control treatment, which had (16.33, 11.67, 9) eggs successively. On the other hand, the aquatic extract of mustard seeds showed effectiveness after (24 ،48، 72) (h) with egg hatching percentages of (68, 58.67, 25) compared to the control treatment, which had (16.33, 11.67, 9) eggs successively. Additionally, the Alcoholic extract of root at 1.5% concentration demonstrated efficacy in inhibiting egg hatching after (24 ,48, 72)(h) with counts of (76, 49.67, 30)eggs successively compared to the control treatment, which had (16.33, 11.67, 9) eggs. The alcoholic extract of mustard seeds at 1.5% concentration also exhibited effectiveness against the viability of second-stage juveniles (J2) after (24 ,48, 72) (h), with counts of (92.33, 76.67, 40) juveniles successively compared to the control treatment, which had (23, 17, 9.67) juveniles. Similarly, the aquatic extract of mustard seeds at 1.5% concentration showed efficacy against the viability of (J2) after (24 ,48, 72) (h), with counts of (68, 72, 31.70) juveniles successively compared to the control treatment, which had (23, 17, 9.67) juveniles. The alcoholic extract of roots at 1.5% concentration also demonstrated effectiveness against the viability of (J2) after (72, 48, 24) (h), with counts of (72, 76.67, 30) juveniles successively compared to the control treatment, which had (23, 17, 9.67) juveniles.